Utilizing waste in circulating cement furnaces - Biernat, Krzysztof; Fuszara, Edward (Studia Ecologiae et Bioethicae, 2003)
The article presents technical and economical possibilities of utilizing normal and liquid waste, including hazardous, through circulating cement furnaces, at the same time complying with environmental protection regulations. Technology for producing cement without waste was presented, by using energetically and chemical aspects of many groups of hazardous substances, including PCB as well as freons. Environmental safe methods of utilizing technical and local waste, normal and liquid, were defined, using cement furnaces and at the same time reducing substantially cement production costs.